A qualitative study on the impact and participation in the AGELESS multidomain intervention: Insights from older adults with cognitive frailty and their caregivers - Ying Qian Ong; Suzana Shahar; A’isyah Mohd Safien; Norhayati Ibrahim; Ai-Vyrn Chin; Francesca Mangialasche; Miia Kivipelto; Devinder Kaur Ajit Singh (BMC Public Health)
Abstract Background Cognitive frailty (CF) is a major precursor to dementia, and multidomain interventions have the potential to delay, prevent or reverse its early onset. However, the successful translation and sustainability of such interventions in real-life settings remain uncertain. In this study, we aimed to explore the insights of older adults with CF and their caregivers regarding the impact and participation in the AGELESS multidomain intervention. Methods This qualitative study was conducted following the completion of AGELESS multidomain intervention. Semi-structured interviews covering domains such as perceptions, benefits, barriers, facilitators, and program preferences were conducted among 17 older adults with CF and 10 caregivers following the completion of the intervention. The data obtained were transcribed verbatim and analyzed using thematic analysis. Each transcript was reviewed and coded to identify prevailing themes derived from the interview data. Results The analysis revealed five distinct themes: (1) impact of the program, (2) facilitators enhancing participation, (3) barriers hindering participation, (4) suggestions for improving participation and (5) challenges to adopt digital platforms. Based on the findings, the AGELESS multidomain intervention had a positive impact on the participants and their caregivers. It was noted that they showed preference for in-person sessions over virtual ones. The study highlighted key factors critical for successful participation, including diversity and inclusivity. It emphasized incorporating a multi-component, group-based approach with social aspects. The intervention should be people-centered, dignified, affordable, and customized to meet the unique needs of each participant. Conclusions The AGELESS multidomain intervention was well received by older adults with CF and their caregivers who participated in this study. Moving forward, it is recommended that future initiatives focus on identifying opportunities to implement existing evidence-based programs on a larger scale for the prevention of dementia in older adults.